Multilevel factors influencing eHealth adoption among older adults during the pandemic - Kim, BoRin; Jeong, Chung Hyeon; Blood, Emily; Arthanat, Sajay; Corvini, Marguerite; Golomski, Casey; Wilcox, John (Frontiers in Public Health, 2025)
IntroductionWhile eHealth became prevalent in healthcare during the pandemic, eHealth adoption by older adults has been slow. This digital divide could lead to worsening health and healthcare disparities. Guided by the push-pull-mooring perspective, this study explored factors influencing eHealth adoption among older adults.MethodsSemi-structured virtual interviews were conducted in 2021 with 31 older adults with healthcare needs. Interviews were thematically coded and analyzed using constant comparative methods.ResultsWe found the pandemic to be a powerful push factor that forced older adults to adopt eHealth along with several pull factors that attracted older adults to use eHealth. A number of mooring factors that made older adults hesitant to adopt eHealth were identified: limited knowledge or skills on eHealth, security concerns, limited technology access, and peer influence.DiscussionsOur findings indicate areas to increase productive use of eHealth within older populations, such as education or support within social networks.